Humoral and cellular responses to SARS-CoV-2 BNT162b2 vaccination in allogeneic hematopoietic stem cell transplantation recipients. Issue 33 (5th August 2022) - Cuffel, Alexis; Maylin, Sarah; Le Buanec, Helene; Delaugerre, Constance; Minier, Marine; Bergerat, David; Merandet, Marine; Cassius, Charles; Peffault de Latour, Régis; Le Goff, Jérôme; Socié, Gérard; Caillat-Zucman, Sophie; et al.
Highlights: All patients had a humoral response to a two-dose mRNA vaccination, with 32% low responders. In responders, neutralizing antibodies percentages were not significantly different between both groups. CD4 + T cell proliferative response could be observed in low serological responders. Abstract: Previous studies reporting the response to SARS-CoV-2 mRNA vaccination in alloHSCT recipients used serological and/or cellular assays, but no study has evaluated vaccine-induced neutralizing antibodies. We prospectively studied 28 alloHSCT recipients who received two BNT162b2 doses. Two patients groups were defined according to time from alloHSCT and immunosuppressive treatment, and had different baseline immunologic status. Study end-point was the evaluation of humoral and cellular responses one month after the second vaccine. All patients seroconverted. Anti-S IgG levels and neutralizing antibodies percentages were not significantly different between both groups. Using IFNγ ELISpot assay, five patients showed a strong increase, without correlation with the humoral response. Using flow cytometry lymphocyte proliferation assay, 14 patients exhibited responding T cells, without difference between both groups or correlation with anti-S IgG levels. A few low serological responders had a detectable CD4 + T cell proliferative response. This finding should be confirmed in a larger cohort.